Bronze Age hoard from Gorenji Suhadol in Gorjanci - Pavlin, Primož; Stipančić, Petra (Arheološki vestnik, 2023)
In 2002, a larger hoard of bronze objects was found on the slopes of Gorjanci, near the village of Gorenji Suhadol. The hoard consists of weapons, tools, jewellery, thin bronze sheet and ingots. The time span of the objects ranges from the Middle Bronze Age to the beginning of the Late Urnfield Period. Comparisons for most of the objects can be found in the hoards of the second phase of the Urnfield period from the Carpathian Basin and the Western Balkans.